The Effect of Entrepreneurship Attitude and Knowledge on Entrepreneurial Intention of Students - Harfandi Harfandi; Zulhelmi Zulhelmi; Era Sonita (EKONOMIKA SYARIAH : Journal of Economic Studies, 2022)
Intention in entrepreneurship is the basis in the formation of the entrepreneurial spirit of students, while intention in entrepreneurship itself can be influenced by entrepreneurial knowledge. For this reason, FEBI UIN Bukittinggi students are expected to be able to master entrepreneurial knowledge as a provision in entrepreneurship, which can be obtained through; entrepreneurship training, entrepreneurship practicum, and Student Entrepreneurship Program (PWM) held by the institution. The purpose of this study was to examine and analyze the effect of entrepreneurial attitudes and knowledge on entrepreneurial intention in FEBI UIN Bukittinggi students. The research sample was drawn by quota random sampling based on a balanced proportion of the existing study programs at FEBI. Respondents are students who will graduate (at least semester IV for DIII, and semester VI for S1), for the three study programs contained in FEBI UIN Bukittinggi, totaling 136 people. The results showed that entrepreneurial attitude had no effect on entrepreneurial intention, while entrepreneurial knowledge had an influence on entrepreneurial intention in FEBI UIN Bukittinggi students. Minat berwirausaha menjadi dasar dalam pembentukan jiwa kewirausahaan mahasiswa, sedangkan  minat berwirausaha itu sendiri  dapat dipengaruhi oleh pengetahuan kewirausahaan. Untuk itu mahasiswa FEBI UIN Bukittinggi diharapkan dapat menguasai pengetahuan kewirausahaan sebagai bekal dalam berwirausaha, yang dapat diperoleh  melalui;  pelatihahan kewirausahaan, pratikum kewirausahaan, dan Program Wirausaha Mahasiswa (PWM) yang diadakan oleh lembaga. Tujuan penelitian ini adalah untuk untuk menguji dan menganalisa pengaruh sikap dan pengetahuan kewirausahaan terhadap minat berwirausaha mahasiswa FEBI UIN Bukittinggi. Adapun sampel penelitian ditarik dengan quota random sampling berdasarkan proporsi berimbang pada program studi yang ada pada FEBI. Responden adalah mahasiswa yang akan diwisuda (minimal semester IV untuk DIII, dan semester VI pada S1), untuk tiga program studi yang terdapat pada FEBI UIN Bukittinggi yang berjumlah 136 orang. Hasil penelitian memperlihatkan bahwa sikap kewirausahaan tidak memiliki pengaruh pada minat berwirausaha, sedangkan pengetahuan kewirausahaan memiliki pengaruh terhadap minat berwirausaha mahasiswa FEBI UIN Bukittinggi.